Digital resources in praxis and research in humanistic translation: The case of the BDAFRICA database - Fernandez-Ruiz, Maria (Comares, 2023)
This research highlights the need for a revolution in the convergence between Humanistic Translation and Digital Humanities. It is true that the Translation practice has already led the inclusion of electronic resources, such as cat tools. However, it has not been a natural path for Humanistic Translation, which is now entering the Digital Humanities along with many other disciplines which have discovered an endless fractal of possibilities in this emerging field. We have materialized one of these possibilities in the creation of the specialized bibliographic database bdafrica, which brings together all the African literature published in Spain in a time span of forty-seven years (1972- 2019). The result allows us to offer, in an unprecedented way, the shaping of the African canon in Spain. bdafrica exponentially multiplies its value due to the fact that it is a free public resource so that it can be used both by publishers and by researchers to promote the growth of Africanist Studies.
New Advances around Humanistic Translation: From Tradition to the Digital Revolution
PUBLISHED
Keywords: Humanistic translation, digital humanities, database, knowledge transfer, quantitative data; Digital Humanities; Translation; Translation studies